2013
DOI: 10.1111/jvp.12042
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and effects of meloxicam, gabapentin, and flunixin in postweaning dairy calves following dehorning with local anesthesia

Abstract: Approved analgesic compounds in cattle are not currently available in the United States due to the lack of validated pain assessment methods and marker residue depletion studies. In this study, we compared the pharmacokinetic parameters and effect of preemptive analgesics administered to calves subjected to dehorning with local anesthesia. Holstein steers were randomly assigned to receive one of the following treatments per os (PO) or intravenously (IV) (n = 8/group): meloxicam (1 mg/kg PO), gabapentin (15 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 53 publications
4
85
0
Order By: Relevance
“…Liquid chromatography-tandem mass spectrometry SP [1][2][3][4][5][6][7][8][9][10][11] Parent substance P molecule composed of 11 amino acids SP [3][4][5][6][7][8][9][10][11] Metabolite of substance P composed of the last 9 C-terminal amino acids SP [7][8][9][10][11] Metabolite of substance P composed of the last 5 C-terminal amino acids been evaluated as a response variable that may be more specific for the measurement of pain in animals. [3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
See 3 more Smart Citations
“…Liquid chromatography-tandem mass spectrometry SP [1][2][3][4][5][6][7][8][9][10][11] Parent substance P molecule composed of 11 amino acids SP [3][4][5][6][7][8][9][10][11] Metabolite of substance P composed of the last 9 C-terminal amino acids SP [7][8][9][10][11] Metabolite of substance P composed of the last 5 C-terminal amino acids been evaluated as a response variable that may be more specific for the measurement of pain in animals. [3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Substance P is a biologically active peptide that has a role in neural transmission of nociceptive signals from peripheral sites to the CNS. 11 Substance P is released by peptidergic peripheral sensory nerve fibers at central synaptic junctions in the dorsal horn of the spinal cord and at peripheral nerve terminals, where the peptide has a role as a signaling molecule in the transmission of pain impulses and the induction of inflammation and central sensitization.…”
Section: Kiu Kallikrein Inhibitor Units Lc-ms-msmentioning
confidence: 99%
See 2 more Smart Citations
“…The numerical difference in ADG between the MEL-GABA group and the PLBO group was surprising because both groups were less active than calves within the MEL group based on the pedometer results. It was recently reported that calves treated with MEL-GABA had a greater ADG after dehorning compared to calves receiving either MEL (P = 0.02) or GABA (P = 0.0006) alone (Glynn et al, 2013). This finding suggests the potential for a synergistic effect of these compounds for improving the growth and performance of calves after a painful event but further research is needed before widespread use can be recommended.…”
Section: Average Daily Weight Gainmentioning
confidence: 98%